THE USE OF COMPUTER TRAINING PROGRAM IN THE FOREIGN LANGUAGE CLASSROOM - Dobizha, N. (Journal of Information Technologies in Education (ITE), 2018)
The article is devoted to the problem of information and communication technologies usage in the foreign language classroom. Some practical recommendations of students’ pedagogical support provided through the computer training program are offered. The article responds to call for principles and teaching practices that address the worldwide problem of various aspects of a foreign language lesson. It draws on educational research and extensive experience with classroom practices to explain important principles for combining the process of speaking teaching, listening skills’ training and grammar practice. In contrast to other subjects the lesson of a foreign language should develop the understanding of languages and cultures through various experiences, fostering a positive attitude toward communication. For this reason, we should follow the individual approach in teaching English. According to this goal we suggest that usage of a training program helps providing harmonious social and psychological interaction between the teacher and his students, choosing the tasks according to the level of each student, organizing various activities in the foreign language classroom, carrying out objective control over the students’ progress.